Effective targeting of STAT5-mediated survival in myeloproliferative neoplasms using ABT-737 combined with rapamycin - Li, Geqiang (2010)
Signal transducer and activator of transcription-5 (STAT5) is a critical transcription factor for normal hematopoiesis and its sustained activation is associated with hematologic malignancy. A persistently active mutant of STAT5 (STAT5a(S711F)) associates with Grb2 associated binding protein 2 (Gab2) in myeloid leukemias and promotes growth in vitro through AKT activation. Here we have retrovirally transduced wild-type or Gab2(−/−) mouse bone marrow cells expressing STAT5a(S711F) and transplanted into irradiated recipient mice to test an in vivo myeloproliferative disease (MPD) model. To target Gab2-independent AKT/mTOR activation, wild-type mice were treated separately with rapamycin. In either case, mice lacking Gab2 or treated with rapamycin displayed attenuated myeloid hyperplasia and modestly improved survival, but the effects were not cytotoxic and were reversible. To improve upon this approach, in vitro targeting of STAT5-mediated AKT/mTOR using rapamycin was combined with inhibition of the STAT5 direct target genes bcl-2 and bcl-X(L) using ABT-737. Striking synergy with both drugs was observed in mouse BaF3 cells expressing STAT5a(S711F), TEL-JAK2, or BCR-ABL and in the relatively single agent-resistant human BCR-ABL positive K562 cell line. Therefore, targeting distinct STAT5 mediated survival signals, e.g. bcl-2/bcl-X(L) and AKT/mTOR may be an effective therapeutic approach for human myeloproliferative neoplasms.